2004
DOI: 10.1145/986710.986727
|View full text |Cite
|
Sign up to set email alerts
|

A study to investigate the impact of requirements instability on software defects

Abstract: Software development is a dynamic process and is characterized by change. Software projects often begin with unclear, ambiguous, and incomplete requirements which give rise to intrinsic volatility. Constant change in requirements is one of the main causes of software defects and a major issue faced by the software industry. This paper describes the findings of our research-based study that investigates the impact of both the pre-release and post-release requirements changes on overall defects by defining measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 13 publications
0
40
0
1
Order By: Relevance
“…Studies show that requirements volatility has a high impact on project performance [40,44]. Several aspects of requirements volatility have been studied, for example its impact on project or process performance [2,14,21,30,33,39,40,44], assessment and prediction [1,7,8,19], simulation models [14,33], and sources and causes of volatility [17,31,39,40]. Zowghi and Nurmuliani [44] perform an empirical study on requirements volatility and its impact on project performance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that requirements volatility has a high impact on project performance [40,44]. Several aspects of requirements volatility have been studied, for example its impact on project or process performance [2,14,21,30,33,39,40,44], assessment and prediction [1,7,8,19], simulation models [14,33], and sources and causes of volatility [17,31,39,40]. Zowghi and Nurmuliani [44] perform an empirical study on requirements volatility and its impact on project performance.…”
Section: Introductionmentioning
confidence: 99%
“… Requirement instability: defined as requirements that fluctuate between the earlier and later stages, and differ at the start and end of the project [8][37] [39].…”
Section: Requirements Volatilitymentioning
confidence: 99%
“…The majority of software development projects in the USA will take longer, cost more than planned and result in "out of specification" products that fail to meet user requirements [11]. Moreover, a report on a survey of over 3800 organizations in 17 European countries concluded that more than 50% of the perceived software problems were in the area of requirements specification and requirements management [12]. Based on this evidence, it can be stated that requirements are very important and it should be given extra attention because it leads to the successful of a software development project.…”
Section: Reviewmentioning
confidence: 99%